Performance Analysis of Bank Syariah Indonesia and Bank Muamalat Indonesia during the COVID-19 Pandemic Reviewed from Maqashid Syariah: Maqashid Sharia Approach Index - Rahmat Fitriansyah; Nurwahidin; Mulawarman Hannase (Prodi Ekonomi Syariah STAI Al-Azhar Menganti Gresik, 2023)
The goal of this research is to measure the capability of Islamic banking in Indonesia during the Covid-19 pandemic using the Maqashid Syariah Index approach and using the measurement of three performance indicators, namely educating individuals, establishing justice, and public interest/maslahah). This research is a type of quantitative descriptive research. Bank Syariah Indonesia and Bank Muamalat Indonesia were used as objects of research. This research uses secondary data that comes from the 2020 and 2021 annual reports sourced from the official website. The maqashid sharia index approach used in data analysis is to calculate the variable performance ratio of the maqashid sharia index which comes from the dimensions of educational grants, research, training, publicity, fair returns, functional distribution, interest-free income, profit ratios, personal income, and investment. in the real sector. The results of this study indicate that overall Indonesian Sharia Banks have the highest score, with advantages compared to using Bank Muamalat in implementing the maqashid sharia aspect and the potential for green finance development